Transformasi Pemasaran Konvensional Ke Digital Marketing Syariah pada Era Society 5.0 di Sektor Perbankan Syariah - Moh. Firdaus Faiz Al'Ula; Elsa Syahrika Salmaria; Sulistyowati Sulistyowati (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
As the world transitions to the era of Society 5.0, the way products are marketed also needs to change. The transformation of marketing from a conventional system to a Sharia-compliant digital marketing system is one way in which economic actors, including Sharia banks, can keep up with the times. This study aims to describe how conventional marketing strategies evolve into sharia-based digital marketing, particularly in the context of sharia banking. The study employs a descriptive qualitative approach, incorporating a literature review and secondary data analysis drawn from publications by the OJK (Financial Services Authority), BI (Bank Indonesia), and sharia bank annual reports. The results show that, by adopting Islamic digital marketing strategies, economic actors are not only profit-oriented, but also benefit and Islamic sustainability-oriented. Digital marketing can expand the reach of promotions, increase Islamic financial literacy among customers, and introduce Islamic banking products to the digital community more effectively and efficiently. Consequently, public trust can be strengthened, Islamic financial inclusion can become more widespread in Indonesia, and businesses can operate in a more comprehensive Islamic manner.